2016
DOI: 10.1371/journal.pone.0148728
|View full text |Cite
|
Sign up to set email alerts
|

30-Day Mortality in Acute Pulmonary Embolism: Prognostic Value of Clinical Scores and Anamnestic Features

Abstract: PurposeIdentification of high-risk patients with pulmonary embolism is vital. The aim of the present study was to examine clinical scores, their single items, and anamnestic features in their ability to predict 30-day mortality.Materials and MethodsA retrospective, single-center study from 06/2005 to 01/2010 was performed. Inclusion criteria were presence of pulmonary embolism, availability of patient records and 30-day follow-up. The following clinical scores were calculated: Acute Physiology and Chronic Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
2
21
0
3
Order By: Relevance
“…However, the study cohort consisted of moderately ill patients and was performed in a pulmonary clinic outside of ICU. Bach et al compared the prognostic yield of different scoring systems and found that APACHE II score performed better than PESI and simplified PESI [19]. The good predictive yield of APACHE II in the critically ill depends on the global assessment of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study cohort consisted of moderately ill patients and was performed in a pulmonary clinic outside of ICU. Bach et al compared the prognostic yield of different scoring systems and found that APACHE II score performed better than PESI and simplified PESI [19]. The good predictive yield of APACHE II in the critically ill depends on the global assessment of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pulmonary embolism is one of the three major cardiovascular diseases along with cardiac and cerebral infarction and it has a high 30-day mortality rate in the order of ten percent (1,2). In general, typical symptoms such as shock, dyspnea and chest pain are caused by central pulmonary emboli at a higher frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Während der ambulanten Weiterbehandlung erhöht sich das Mortalitätsrisiko durch thromboembolische Folgeereignisse und Nebenwirkungen der Therapie, sowie durch Rechtsherzversagen bei Patienten mit persistierender pulmonaler Hypertonie. Die kumulative Mortalität nach 30 Tagen, bezogen auf alle Schweregrade, wird im Mittel mit etwas mehr als 10 % angegeben (4,12,26,58,90).…”
Section: Hintergrundinformationen Zur Lungenembolieunclassified